Effects of lime in combination with water level toward soil chemical properties and paddy growth performance grown on acidic soil / Muhammad Syafri Famin Ahmad Azli and Norazlina Abu Sari - Ahmad Azli, Syafri Famin; Abu Sari, Norazlina (Faculty of Plantation and Agrotechnology, 2018)
A glasshouse study was conducted to determine the effect of lime application rate in combination with water level on soil pH, aluminium (Al) concentration and nutrient availability. The second aim of the study is to determine the optimum combination of lime rate application and water level on paddy growth. Two factors were used for the study which are three lime application rate (no lime application, 1 t/ha CaCO3 and 2 t/ha CaCO3) and two water level (3-5 cm above soil surface and 8-10 cm above soil surface).The preliminary results of the research showed that soil available Al and soil available Ca were significantly different among the treatment. The lowest soil available Al mean was 65.14 mg/kg for treatment L3W2 (2 t/ha CaCO3 and 8-10 cm water level). Meanwhile, the highest mean for soil available Ca was 1061 mg/kg for treatment L3W2. Furthermore, the soil pH result show no significant but the highest mean soil pH was 5.43 for treatment L3W2.The optimum combination of lime application rate and water level was treatment L3W2 with highest soil pH value, highest available Ca and lowest available Al as compared to other treatments.